Development of Vegetable Export Business Model Based on Farmer Partnerships - Sunandar, Muhammad Prayoga; Hasbullah, Rokhani; Asnawi, Yudha Heryawan (JURNAL BISNIS STRATEGI, 2023)
This study examines the development of company's business model, which initially relied on a single supplier to source vegetables, later evolved into a new business model through the introduction of partnerships with farmers, including direct purchasing and growing cabbage on the farm. Financial analysis shows a significant improvement in the company's performance, highlighted by increased revenue and greater social impact. Additionally, the company is now able to meet market demand by shipping 300 containers per year, an unprecedented achievement for the Taiwanese market. Management implications and strategic recommendations include expanding partnerships, capacity building for farmers, commitment to sustainable agricultural development, active market research and diversification of agricultural products.